The Social Representations of Survivors of the Armed Conflict on the Regulatory Reparations Measures in Colombia: the Case of Barrancabermeja - Salas Picón, Wilson Miguel; Pérez Correa, Kethy Luz; Moreno Correa, Julio César; Carrasco Tapias, Nayib; Valenzuela Bonilla, Elsa Beatriz (Revista del CLAD Reforma y Democracia, 2019)
Building peace is a challenge for a country like Colombia that has remained hopeless to achieve it for more than half a century. This requires the participation of all Colombians, especially those victims of serious violations, whose fundamental rights were affected as a consequence of the armed conflict. In order to intervene in this process, the State created the Law 1448 in 2011 to compensate the damages and restore territories. After six years it is important to know the perception and experience of the families affected by displacement and enforced disappearance about the individual and collective reparation contemplated in its articles. To achieve this objective a hermeneutical research took place between 2016 and 2018 with 60 participants from different organizations, associations and collectives from Barrancabermeja, Colombia. Interactive techniques were used -descriptive, historical-narrative, analytical and expressive- and allowed the expression of thoughts, feelings, experiences and appreciations about the Law 1448/2011. In this way the participants illustrated the social representation around the elements of the integral reparation that is supposed to be fulfilled by the Colombian State. The results show that the participants continue under the condition of victims and that they want dignity rather than an economic compensation. They demand the truth and answers to their emotional losses and a State that guarantee non-repetition of violations to the fundamental rights. Furthermore, the results indicate that the regulatory framework must be modified according to the needs demanded by the survivors in terms of rehabilitation and the effective enjoyment of human rights at the individual, collective, material, symbolic and moral level. Only in this way it facilitates the end of the internal armed conflict and the achievement of a stable and lasting peace.